REPRODUCING KERNEL FUNCTIONS FOR DIFFERENCE EQUATIONS - Akgul, Ali; İnç, Mustafa; Karatas, Esra (Amer Inst Mathematical Sciences-Aims, 2015)
In this work, some new reproducing kernel functions for difference equations are found. Reproducing kernel functions have not been obtained for difference equations until now. We need these functions to solve difference equations with the reproducing kernel method. Therefore, these functions are very considerable functions.
Keywords: Reproducing kernel method; difference equations; reproducing kernel spaces